Ethnobotanical study on some useful shrubs of Astore valley, Gilgit-Baltistan, Pakistan (Bangladesh Journal of Botany, 2014)
In Astore valley, 26 species of plants under 17 genera and 13 families were found to be used as folkmedicine. The study reveals that the villagers from remote area use medicinal plants for the treatment of joint pain, bone fracture, urine problem, asthma, diabetes, blood pressure and for the treatment of other common ailments. The aborigines also use traditional herbal therapy for their live stocks. Because of high destruction pressure of anthropogenic origin, Ephedra gerardiana Wallich ex C.A.Meyer, Berberis spp., Rosa foetida Herrm. and Rhododendron hypenanthum Balf. f. were found threatened. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19741 Bangladesh J. Bot. 43(1): 19-25, 2014 (June)